(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2021)
The study deals with the modifications resulting from the addition of § 9º to art. 2º of law nº 12.850/2013. Due to the new wording provided by law nº 13.964/2019, the progression of the regime, conditional release and other prison benefits to those convicted of belonging to a criminal organization or crimes committed through a criminal organization that still maintain an associative bond are prohibited. The problem is to identify whether the prohibition on regime progression is similar to any type of prison system; whether these changes are constitutional and whether human rights are respected. The methodology used is based on the analysis of national and international standards, as well as on doctrine and jurisprudence research. In the end, it appears that the new law is approaching the pensilvanic system or cellular penitentiary system; complies with the principle of individualization of punishment, being constitutional and compatible with the principle of conventionality in international standards, in particular with the United Nations Minimum Rules for the Treatment of Prisoners and the Convention Against Torture and Other Cruel, Inhuman or Degrading Treatment or Punishment.